Examining Ethnic Disparities in Pregnancy Induced Hypertension and Risk Factors in Pregnant Lady Visiting Devdaha Medical College and Research Institute-A Retrospective Study - Thakur, Nishant Kumar; Kumari, `Neha; Roy, `Aanchal; Dubey, Ritesh (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Pregnancy induced hypertension (PIH), a major pregnancy complication marked by high blood pressure, significantly impacts maternal and fetal health. Pre-eclampsia and other pregnancy-related hypertension disorders (Gestational hypertension, Severe pre-eclampsia and eclampsia) falls under the umbrella term "PIH”. Few major risk factors for PIH include extremes in mother age, passive and active smoking, primigravida and multipara (≥5), aided vaginal delivery, elective cesarean section. The aim of this study is to assess the prevalence of PIH, identify and compare the risk factors associated with it across different ethnicities and assess potential influences of socioeconomic factors and life style habits. Method: This was a retrospective study conducted in 174 reproductive age female of 18-42 years age who delivered by any mode in obstetrics & gynecology department of Devdaha Medical College and Research Institute, Rupandehi, Nepal. Data regarding demographics, socioeconomic status, obstetrics, were obtained from hospital records. The data was analyzed in SPSS version 16. Result: No significant associations were found between PIH and several maternal or obstetric factors like Religion, ethnic group etc., severe cases were clearly linked to adverse fetal outcomes such as IUFD and stillbirth. Conclusion: Women with lower socioeconomic status are less likely to take folic acid supplements, and more effort should be made to increase their awareness of the importance of supplementation. Unplanned pregnancy is another strong risk factor for not supplementing with folic acid, and thus should be avoided. But there seems to be no association between parity, maternal education status and religion in the intake of folic acid.